Comparison of Minimally Invasive Carpal Tunnel Release with Open Carpal Tunnel Release - Syed Aamir Shah, Faizullah Khan, Hamza Ejaz, Rayif Rashid Kanth, Waseem Ahmed, Zara Qureshi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the long-term results of conventional treatment [open carpal tunnel release (OCTR)] with the results of mini-open carpal tunnel release surgery (MCTR), performed through the palmar approach. Study design: retrospective study Place and Duration: This study was conducted at Pakistan Institute of Medical Sciences Islamabad from June 2020 to June 2022 Methodology: This research involves a total of 40 patients who were divided into 2 groups. Each group contained 20 patients respectively. One group was treated with mini-open carpal tunnel surgery and the other was treated with conventional treatment. Each patient had to conduct follow-ups for at least one years. The results were evaluated through SSS (Symptom Severity Scale), VAS (Visual Analogue Scale), DASH Score (Disability of arms, shoulder and hand), and FSS (Functional Status Scale). For a statistical analysis, confidence interval of 95% was set and significance was 0.05. Results: In the long-term follow-up, both groups showed comparable results. The mean follow-up for MCTR and conventional method was 2 years. The DASH score was 4.2 and 8.9, SSS was 1.2 and 1.1, VAS was 0.5 and 0.9, and the FSS was 1.4 and 1.1. The scar sensitivity was lower in MCTR. It was 5 percent in MCTR while 12 percent in conventional treatment. The pain, time taken in surgery, and recovery time were also lower in the MCTR group. Both groups showed less complications and there was not a single recurrence. Practical implication : To compare the long-term results of conventional treatment [open carpal tunnel release (OCTR)] with the results of mini-open carpal tunnel release surgery (MCTR), performed through the palmar approach. Practically less invasive surgery (minimal invasive) is more beneficial for patient in terms of wound complications Conclusion: Mini-open carpal tunnel release is a better option than the conventional treatment. It is a fast, reliable, and simple process which relieves the patient from scar sensitivity. Keywords: Mini-open carpal tunnel release, open carpal tunnel release, carpal tunnel syndrome